2016
DOI: 10.1200/jco.2015.64.2702
|View full text |Cite
|
Sign up to set email alerts
|

Trial Design and Objectives for Castration-Resistant Prostate Cancer: Updated Recommendations From the Prostate Cancer Clinical Trials Working Group 3

Abstract: Purpose Evolving treatments, disease phenotypes, and biology, together with a changing drug development environment, have created the need to revise castration-resistant prostate cancer (CRPC) clinical trial recommendations to succeed those from prior Prostate Cancer Clinical Trials Working Groups. Methods An international expert committee of prostate cancer clinical investigators (the Prostate Cancer Clinical Trials Working Group 3 [PCWG3]) was reconvened and expanded and met in 2012-2015 to formulate updated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
986
0
30

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 1,250 publications
(1,027 citation statements)
references
References 66 publications
11
986
0
30
Order By: Relevance
“…Our model was also predictive for time on treatment, a useful surrogate in the real-world setting for the duration of clinical benefit on treatment and an important endpoint, as highlighted in the updated recommendations on trial design and objectives from the Prostate Cancer Working Group 3. 16 These findings demonstrate that our model is predictive of outcomes on abiraterone and thus may be valuable in selecting patients likely to benefit from first-line abiraterone, and identifying those for whom alternate treatments could be considered, such as first-line chemotherapy or clinical trials. A key strength of the 6-factor prognostic index model is that it is a pragmatic tool for risk stratification utilising easily available (and inexpensive) clinical parameters.…”
Section: Cuaj -Original Research Khalaf Et Al Stratifying Clinical Oumentioning
confidence: 68%
“…Our model was also predictive for time on treatment, a useful surrogate in the real-world setting for the duration of clinical benefit on treatment and an important endpoint, as highlighted in the updated recommendations on trial design and objectives from the Prostate Cancer Working Group 3. 16 These findings demonstrate that our model is predictive of outcomes on abiraterone and thus may be valuable in selecting patients likely to benefit from first-line abiraterone, and identifying those for whom alternate treatments could be considered, such as first-line chemotherapy or clinical trials. A key strength of the 6-factor prognostic index model is that it is a pragmatic tool for risk stratification utilising easily available (and inexpensive) clinical parameters.…”
Section: Cuaj -Original Research Khalaf Et Al Stratifying Clinical Oumentioning
confidence: 68%
“…Although the cohort studied was small, Antonarakis et al (13) reported that the AR-V7 expression level in CTCs was prognostic of the outcomes of CRPC treatment. Further studies using liquid biopsies that include CTCs and cell-free DNA are warranted to establish robust biomarkers, which were cited in PCWG3 (24).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of recommendations within the new PCWG3 guidelines that reflect the increased understanding of prostate cancer heterogeneity. 19 • In recognition of the significant phenotypic heterogeneity of prostate cancer, it has been recommended that dedicated trials should be designed for different groups of prostate cancer patients, defined by their pattern of spread.…”
Section: Resultsmentioning
confidence: 99%